2023
DOI: 10.1038/s41537-022-00325-w
|View full text |Cite
|
Sign up to set email alerts
|

Predicting aging trajectories of decline in brain volume, cortical thickness and fractional anisotropy in schizophrenia

Abstract: Brain-age prediction is a novel approach to assessing deviated brain aging trajectories in different diseases. However, most studies have used an average brain age gap (BAG) of individuals with schizophrenia of different illness durations for comparison with healthy participants. Therefore, this study investigated whether declined brain structures as reflected by BAGs may be present in schizophrenia in terms of brain volume, cortical thickness, and fractional anisotropy across different illness durations. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 77 publications
(124 reference statements)
0
8
0
Order By: Relevance
“…Previous studies on brain-age prediction have also demonstrated that individuals with schizophrenia exhibit deviations in brain aging trajectories, as indicated in both T1-weighted magnetic resonance imaging (MRI) [16][17][18][19][20][21][22][23][24] and DTI [25,26] findings. The recent studies used multimodal MRI to evaluate the brain age gap in patients with schizophrenia and obtained results consistent with those of studies using a single neuroimaging modality [27][28][29][30].…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…Previous studies on brain-age prediction have also demonstrated that individuals with schizophrenia exhibit deviations in brain aging trajectories, as indicated in both T1-weighted magnetic resonance imaging (MRI) [16][17][18][19][20][21][22][23][24] and DTI [25,26] findings. The recent studies used multimodal MRI to evaluate the brain age gap in patients with schizophrenia and obtained results consistent with those of studies using a single neuroimaging modality [27][28][29][30].…”
Section: Introductionmentioning
confidence: 52%
“…Brain-age studies have indicated that individuals with schizophrenia had a brain age that was older than those of HCs in the FA-based model [25,26]. Our recent study suggested that there were nonsignificant differences in the global brain age gap between participants with schizophrenia and healthy controls across different illness durations in the FA model [30]. The possible reason is that computing the global brain age gap might reduce the sensitivity for detecting the deviation of aging trajectories of individual white matter tracts.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous research has demonstrated that cortical thickness age-dependently declines across the adult life span (64-67). Notably, both GM volume and cortical thickness are key features in many brain age models (25,68), and cortical thickness has shown some of the largest disparities in brain age across different durations of illnesses (69). Consequently, the regions with reduced cortical thickness identified in our study might be the main drivers of accelerated brain aging in individuals with CUD.…”
Section: Discussionmentioning
confidence: 73%
“…It is hypothesized that the deterioration of cortical thickness is a driving factor behind reductions in brain volume (69,70). However, it is important to note that these are speculative assumptions, as several other factors such as cortical surface area, gray/white matter intensity contrast, and curvature may collectively contribute to changes in brain volume (69,70). Further investigations are needed to comprehensively understand the complex interplay of these factors.…”
Section: Discussionmentioning
confidence: 99%